LITERATURE REVIEW ON QUALITY WORK LIFE OF EMPLOYEES: A CASE STUDY ON SOUTHCO UTILITIES - Padhy, Tara Prasad; Panda, Lakshmi Prasad; Mohapatra, Pravash Ranjan (International Journal of Psychosocial Rehabilitation, 2020)
Quality of work life of employees is an important concept in today's organisation and its environment. This study therefore focuses on the concept of quality of work life by carrying out a detailed literature review analysis on the same topic. Various online articles peer reviewed journals and online books are considered to carry out the literature review analysis. This secondary data are collected and reviewed in order to understand the concept of quality of work life within Southco Utilities organisation. The importance of quality of work life is overviewed along with the eight scopes of QWL. Further the impacts and factors of QWL are reviewed in order to understand how the employees of the organisation are affected. After a detail reviewing of the existing literature, the gap in the literature is conducted in order to understand the areas that needs to be focused so as to achieve a better and higher detailed outcome of the study. Finally, a conceptual framework is provided to understand and identify the research gaps and potential biases present within the research. It is further used to arrive at a particular hypothesis for this conducted research.